Monetary and economic union in West Africa: An analysis on trade - Isaac Mensah (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2015)
Purpose-This paper makes an analysis of trade in the WAMZ as well as the WAMZ's trade with other countries in West Africa, Europe and Asia based on the Optimal Currency Area (OCA) theory. This theory first proposed by Mundell (1961) as a basis for evaluating whether or not an area constitutes an optimal currency area is exploited in assessing whether or not the WAMZ constitutes an OCA. Methodology/Design/Approach-Data utilized for the trend analysis were sourced from the World Bank's World Development indicator (WDI) and annual reports of the central bank of each WAMZ member country considered. The data spans from 2002 to 2013 and it covers five (5) WAMZ member countries. Similarly, data for the trade analysis was sourced from the World Bank's World Integrated Trade Solution (WITS) and it for the period 2000 to 2012. Findings-While, I found strong evidence against trade symmetry in the WAMZ, there are some evidence of marginal convergence in inflation, real GDP growth and monetary policy rate. Moreover, while I found reasons to believe that the convergence is partially as a result of the convergence criteria, trade in WAMZ remains significantly low and more so for WAMZ's trade in West Africa. Originality/value-This paper concludes that on the basis of trade, WAMZ does not qualify as an OCA. This means that more time is needed for convergence of intra WAMZ trade and in this regard, this paper supports the WAMI's declaration of achieving integration in the year 2020.
Keywords: F15; F33; G15; 330; integration; monetary union; convergence criteria; WAMZ